Continuous fluorescence recording as a way to improve Pacific oyster (Crassostrea gigas) models of paralytic shellfish toxin accumulation - Baron, Regis; Couedel, Marielle; Joret, Camille; Garen, Pierre; Truquet, Philippe; Masselin, Pierre; Bardouil, Michele; Lassus, Patrick (EDP Sciences, 2006)
A simple system was used to simulate the effect of alternating toxic (paralytic shellfish poisoning toxins) and non-toxic microalgal diets on oyster feeding behaviors and rates of toxin accumulation. These experimental conditions were meant to reflect, to some extent, the incoming and outgoing fluxes of toxic algae observed at the mouth of the Penze estuary (Northern Brittany, France). Physiological and toxicological parameters were estimated based oil fluorescence measurements recorded continuously at the outlet of each experimental tank, which contained a single oyster. Q(tox), this variable describes toxin uptake in oysters, it was used (instead of the toxin ingestion rate): i) in simple graphical analyses, ii) as well as in one- and two-compartment models. Results Show that toxin Uptake varies widely from one individual to another and is not proportional to the concentration of toxic algae in sea water. A one-compartment model with individual fluorescence recordings as "input" data gave questionable results, however, a two-compartment model was found to effectively describe coil lamination kinetics ill oysters. Limitations of this model as well as possible improvements are discussed. Un système simplifié est utilisé pour simuler l'effet d'un régime alimentaire alterné toxique et non toxique sur le comportement alimentaire et le taux d'accumulation de toxines chez l'huître. Ces conditions expérimentales ont pour objectif de restituer, autant que possible, les flux entrants et sortants d'algues toxiques dans l'embouchure de la rivière de Penzé (Bretagne Nord, France). Des paramètres physiologiques et toxicologiques sont évalués sur la base de mesures continues de fluorescence à la sortie de chaque bac expérimental contenant une huître. La variable , est utilisée (et non le taux d'ingestion), elle décrit la prise de toxine prélevée par l'huître dans le milieu pour : i) des analyses graphiques simples et ii) établir des modèles à un et deux compartiments. Les résultats montrent que la prise de toxine varie ...